2016
DOI: 10.1371/journal.pntd.0004579
|View full text |Cite
|
Sign up to set email alerts
|

Faecal Parasitology: Concentration Methodology Needs to be Better Standardised

Abstract: AimTo determine whether variation in the preservative, pore size of the sieve, solvent, centrifugal force and centrifugation time used in the Ridley-Allen Concentration method for examining faecal specimens for parasite stages had any effect on their recovery in faecal specimens.MethodsA questionnaire was sent to all participants in the UK NEQAS Faecal Parasitology Scheme. The recovery of parasite stages was compared using formalin diluted in water or formalin diluted in saline as the fixative, 3 different por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 4 publications
1
34
0
9
Order By: Relevance
“…Single, 41.7-mg thick, Kato-Katz smears were prepared from each stool sample on the same day of specimen collection. Then, 1 g of stool was preserved in 10% formalin solution and processed using the formalin-ether concentration technique (35). The slides were examined by three experienced laboratory technicians.…”
Section: Methodsmentioning
confidence: 99%
“…Single, 41.7-mg thick, Kato-Katz smears were prepared from each stool sample on the same day of specimen collection. Then, 1 g of stool was preserved in 10% formalin solution and processed using the formalin-ether concentration technique (35). The slides were examined by three experienced laboratory technicians.…”
Section: Methodsmentioning
confidence: 99%
“…Total hands-on time including preparation for the extended method in our is setting estimated to 7-12 min per sample which is less than reported by others [57]. Time of examination per slide is dependent both on the experience and competence of the microscopist, but also on the amount of faecal debris, and optimization of the properties of FEC can decrease time [47] and also, experience decrease time spent per sample. The addition of more staining can be optimized by staining in batch, so that all steps only need to be done once.…”
Section: Discussionmentioning
confidence: 51%
“…The amount of Cryptosporidium oocysts in this study varied from multiple per vision field to a few per slide. It is important for sediments to have a minimum of faecal debris, especially when detecting the small Cryptosporidium and the properties of FEC vary and several factors influence the ability to decrease faecal debris in the sediment and thereby the result, for instance centrifugation time and speed, filtration pore size, preservative and sample quality [47]. The use of metal sieves may have improved yield, studies have shown that Cryptosporidium can end up in the gauze that is traditionally used for filtration [48], but it was not part of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the rate of positive stool tests differed markedly according to the laboratory performing the testing (ranging from 0.0% to 6.7%; data not shown). Previously, Manser et al also demonstrated that variations in the procedures for stool examinations could reduce the recovery of parasites at different stages, particularly if present in small numbers [5]. We suggest that the standardization of stool examinations in regards to the overall methodology and QC is needed.…”
Section: 국내 검사실에서의 대변 검경 검사에 대한 내부정도관리 현황mentioning
confidence: 79%
“…Most of the responses were from laboratories in medical institutions with 500-1,000 beds (53.8%, 21/39), followed by seven institutions with less than 200 beds (including three referral medical laboratories), seven institutions with 200-500 beds, and four institutions with greater than 1,000 beds (Table 1). Fecal concentration is recommended to increase the chance of detecting parasitic ova, cysts, and larvae, particularly in specimens where they are present in insuf cient numbers to be seen using direct microscopy [5]. Although more than a half of the laboratories (51.3%) performed stool concentration using formalin-ether or Tween 80, a third of the laboratories (30.8%) performed direct smears only.…”
Section: 국내 검사실에서의 대변 검경 검사에 대한 내부정도관리 현황mentioning
confidence: 99%